Beverages and Desserts With Therapeutic and Prophylactic Properties Based on Alginate-Containing Biogel From Laminaria – ``Vitalgar Cardio’’ - Kotelnikova, Liliya Kh.; Podkorytova, Antonina V.; Roshchina, Anna N.; Shashkina, I.A. (KnE Life Sciences, 2022)
In this research, recipes were developed for beverages and desserts based on ”Vitalgar Cardio”, abiogelthat contains alginate, has therapeutic and prophylactic properties, and was produced from laminaria at the SPC ”Vita-Li” LLC. ”Vitalgar Cardio”, in its liquid form, as well as desserts based on it, is a source of soluble dietary fiber (alginates) and chemical elements such as potassium, magnesium and iodine, and is an adsorbent of various toxins, including radionuclides and heavy metals. The developed products have traditional appeal, with a focus on healthy nutrition, which is currently being promoted among the population. Keywords: Lamibaria, Alginate, Fucoidan